IMPLEMENTASI MEDIA PEMBELAJARAN MIND MAPPING BERBASIS ANDROID UNTUK MENINGKATKAN DAYA JUANG DAN PEMECAHAN MASALAH IPA MAHASISWA - Rita Herlina Br PA; Siti Zahara H. Harahap (JURNAL CURERE, 2021)
This study aims to describe and see the effect of implementing Android-based mind mapping learning media on the fighting power and problem-solving abilities of PGSD University Quality Science. This type of research is quasi-experimental research (quasi-experiment). The sample in this study was class 2A11 consisting of 22 people and class 2A12 consisting of 20 people. The research instruments used were tests and observation sheets of fighting power. The data analysis technique used is an independent test between two factors. Based on data analysis and hypothesis testing, it was found that: (1) There was an increase in the fighting power of Quality University PGSD students after the implementation of Android-based mind mapping learning media (2) The ability to solve science in PGSD University Quality students after the implementation of Android-based mind mapping learning media obtained an average value of Average: 81.25 (3) There is a significant effect through the application of Android-based mind mapping learning media on the fighting power and ability to solve science problems in PGSD University Quality students.